CONSTRUCTION OF SAILWING ROTOR (VERTICAL) FOR PUMPING WATER IN BANGLADESH - Ashraf, Asif; Autul, Yashdi Saif; Talukder Nazib, Md.Shah Arman Alam (DEPARTMENT OF MECHANICAL ENGINEERING, 2021)
From the Recent years perceptions, obviously Fossil fuels are going to either be gone or they will turn out to be excessively costly, making it impossible to sensibly utilize and furthermore, the atmosphere is changing and that non-renewable energy source emissions are contributing enormously to that change. Improvement of wind energy used in urban situations is of developing enthusiasm to industry and local governments as a alternative option to utility-based and non-renewable types of energy creation and also wind turbines produce zero outflows in their generation of power. To lessen the present utilization of power for pumping water and to guarantee of drawing water in the territory where transmission of power is too exorbitant, development of sailwing rotor (vertical) is valued. To use the accessible wind energy a vertical axis sailwing rotor having six sails combined with a diaphragm pump is created utilizing locally accessible material and innovation which works even at low and variable air speed.